2021
DOI: 10.26444/monz/138621
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression in men – a common but rarely understood problem

Abstract: Introduction. Postpartum depression (PPPD) is defined as the occurrence of a depressive episode in the postpartum period, with a peak incidence between 3-6 months. It is estimated that 1 in 10 fathers are currently affected, yet most research focuses only on postpartum depression in mothers. Objective. The aim of the study was to analyze scientific reports on paternal postpartum depression in men. The available literature on 'postpartum depression among men' was reviewed based on the Scopus, PubMed and OVIDMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For programs targeting additional health domains, there was evidence that PN also fostered improvements in health behaviors, such as a reduction in smoking or opioid use (Cochran et al., 2018; Fallin‐Bennett et al., 2019), and improvements in diet and exercise (Simione et al., 2021). Despite the availability of effective treatments for PMH issues, prior research has identified a range of factors that hinder screening rates (Leśniewska et al., 2021; Lomonaco‐Haycraft et al., 2019) and adequate treatment (Austin et al., 2017; Cox et al., 2016; Thombs et al., 2014). The potential of PN to enhance patients’ service utilization, therefore, provides a promising model for tackling these issues in PMH service provision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For programs targeting additional health domains, there was evidence that PN also fostered improvements in health behaviors, such as a reduction in smoking or opioid use (Cochran et al., 2018; Fallin‐Bennett et al., 2019), and improvements in diet and exercise (Simione et al., 2021). Despite the availability of effective treatments for PMH issues, prior research has identified a range of factors that hinder screening rates (Leśniewska et al., 2021; Lomonaco‐Haycraft et al., 2019) and adequate treatment (Austin et al., 2017; Cox et al., 2016; Thombs et al., 2014). The potential of PN to enhance patients’ service utilization, therefore, provides a promising model for tackling these issues in PMH service provision.…”
Section: Discussionmentioning
confidence: 99%
“…Despite increased awareness of perinatal mental health (PMH) issues and the availability of effective treatment options, many women are not screened for MH as part of perinatal care or do not receive treatment for their distress. Screening and treatment rates are estimated to be significantly lower for members of vulnerable groups, those in the private health care system, and among fathers or parenting partners (Leśniewska et al., 2021; Lomonaco‐Haycraft et al., 2019). Even with policy initiatives aimed at implementing universal PMH screening, many women identified as at risk either do not access MH assessment and treatment services, do not follow through with treatment or are inadequately treated, due to a range of factors including lack of appropriate services, stigma, and difficulty navigating a fragmented PMH service landscape (Austin et al., 2017; Cox et al., 2016; Thombs et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to conduct further research and strive to include this group in screening, increasing the likelihood of getting help and improving the quality of functioning of the woman's partner and the whole family [16]. Against this background, it has been indicated that the male version of the EPDS questionnaire may find application as a type of screening applied to the partners of pregnant and postpartum women [17].…”
Section: Figure 1 Prevention and Diagnostic Activities Carried Out By...mentioning
confidence: 99%
“…There may also be an inadequate fear for the child's health and life, excessive worrying about the situation and excessive concern for one's own health (Wasilewska-Pordes, 2000). However, the above-mentioned symptoms are considered more typical of maternal PPD, which is dominated by depressed mood and apathy, while PPPD is additionally accompanied by aggressiveness, irritability, indecisiveness, and restricted range of emotion (Madsen & Juhl, 2007) or isolation from the environment (Leśniewska et al, 2021) and resorting to substance use as well (Dhillon et al, 2022).…”
Section: Introductionmentioning
confidence: 99%